Hydrophobic Noble Metal Nanoparticles: Synthesis, Characterization and Perspectives as Gas Sensing Materials. (2015) - Bearzotti, A.; Fontana, L.; Fratoddi, I.; Venditti, I.; Testa, G.; Rasi, S.; Gatta, V.; Russo, M.V.; Zampetti, E.; Papa, P.; Macagnano, A.
Abstract: Noble metal nanoparticles (MNPs) with controlled diameters in the range 5-15 nm, have been prepared by chemical wet reduction reactions starting from Au precursor in the presence of bifunctional thiolate, i.e. biphenyl-4, 4′-dithiol. MNPs have been deposited on electrospinned titania nanofibers by dipping. The composite has been investigated at room temperature in resistive type device under UV irradiation. IV curves show properties of photoconduction and upon exposure towards sulphur dioxide (SO2 ) a sensing behaviour has been observed. The devices shoved an exponential decay for increasing values of SO2 concentration.